2020
DOI: 10.1002/chem.202003220
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Mn Doped Ni‐MOF Nanosheet Array for Highly Capacitive and Stable Asymmetric Supercapacitor

Abstract: In this study, we demonstrate that an Mn‐doped ultrathin Ni‐MOF nanosheet array on nickel foam (Mn0.1‐Ni‐MOF/NF) serves as a highly capacitive and stable supercapacitor positive electrode. The Mn0.1‐Ni‐MOF/NF shows an areal capacity of 6.48 C cm−2 (specific capacity C: 1178 C g−1) at 2 mA cm−2 in 6.0 m KOH, outperforming most reported MOF‐based materials. More importantly, it possesses excellent cycle stability to maintain 80.6 % capacity after 5000 cycles. An asymmetric supercapacitor device utilizing Mn0.1‐N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…This could be explained interpreted that Co 2+ partially replaced Ni 2+ in the metal–organic framework, retaining the crystal structure of C 8 H 6 NiO 5 ·H 2 O. 25,29,30 …”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…This could be explained interpreted that Co 2+ partially replaced Ni 2+ in the metal–organic framework, retaining the crystal structure of C 8 H 6 NiO 5 ·H 2 O. 25,29,30 …”
Section: Resultsmentioning
confidence: 82%
“…2(e), the O 1s spectrum was deconvoluted into two peaks at 530.8 and 533 eV, which were associated with the C-O and metal-oxygen bonds M-O-M, respectively. 25,33 The C 1s spectrum (Fig. 2(f)) showed two peaks at 288.6 and 284.8 eV, which were associated with the O-C]O, C-C bonds of terephthalate, respectively.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a practical device employing Mn 0.1 -Ni-MOF/NF (positive electrode) and activated carbon (negative electrode) as electrodes attain a huge energy density and power density of 39.6 Wh/kg and 143.8 W/kg, respectively. 173 In the case of Ni-based compound it has been observed that electrochemical response of Ni based MOF is superior to Co-Based MOF due to better conductivity and transformation of Ni-MOF into Ni (OH) 2 work as a catalyst for electrochemical activity. As compared to single metal MOF, the incorporation of second metal results in improved conductivity of MOF without calcination process.…”
Section: Ni-based Mofs Composites and Mofs Derived Materialsmentioning
confidence: 99%